2007
DOI: 10.1007/s00068-007-7112-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute Traumatic Fibular Bowing Associated with Ankle Fracture

Abstract: We present a case of traumatic fibular bowing associated with ankle fracture in a 14-year-old girl. Acute traumatic bowing deformities of the fibula have always been reported as associated with mid-shaft tibial fractures, but involvement of the distal fibula associated with an ankle fracture has not been reported. The clinical picture is described and the mechanism of injury discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Medial KOA Associated with Upper Fibular Curvature is an Optimal Indication for PFO Previous studies have reported that fibular curvature is mainly associated with traumatic tibial fractures [33][34][35] . However, our published studies demonstrated that upper fibular curvature was associated with greater fibular axial loading forces and was taken as an anatomical adaptation of the progression of medial compartment KOA 7 .…”
Section: Alignment Correctionmentioning
confidence: 99%
“…Medial KOA Associated with Upper Fibular Curvature is an Optimal Indication for PFO Previous studies have reported that fibular curvature is mainly associated with traumatic tibial fractures [33][34][35] . However, our published studies demonstrated that upper fibular curvature was associated with greater fibular axial loading forces and was taken as an anatomical adaptation of the progression of medial compartment KOA 7 .…”
Section: Alignment Correctionmentioning
confidence: 99%